Electroactivation-induced spinel ZnV2O4 as a high-performance cathode material for aqueous zinc-ion battery. (January 2020) - Liu, Yi; Li, Chang; Xu, Jia; Ou, Mingyang; Fang, Chun; Sun, Shixiong; Qiu, Yuegang; Peng, Jian; Lu, Gongchang; Li, Qing; Han, Jiantao; Huang, Yunhui
Abstract: Rechargeable and affordable aqueous zinc-ion batteries (ZIBs) with high energy density are needed for large-scale energy storage systems. However, the development of ZIBs has stagnated due to the lack of stable high-capacity cathode materials. Here, a typical spinel ZnV2 O4 has been investigated as a ZIB cathode, and a significant electroactivation reaction was observed during the initial electrochemical cycles. After electroactivation, ZnV2 O4 exhibits a high reversible capacity of 312 mAh g −1 and retains a capacity of 206 mAh g −1 over 1000 cycles at a high rate of 10 C. The electroactivation process was then analyzed via in-situ XRD, ex-situ PDF, ex-situ HADDF-STEM, ex-situ XPS, and various electrochemical measurements. The electroactivation enhances the surface electrochemical reaction with self-adaptive adjustment of the lattice structure. This guarantees outstanding electrochemical performance. The encouraging results deepen our understanding of rechargeable aqueous batteries and offer insight into the design of high-performance electrode materials for rechargeable aqueous ZIBs. Graphical abstract: A typcial spinel ZnV2 O4 is successfully fabricated for aqueous zinc-ion battery, its special electrochemical activation mechanism accompanyed by micro-crystallization leads to an enhanced surface reaction and local lattice distortion, results in a superior specific capacity, rate performance and long-term stability. This could extend a new avenue toward the rechargeable aqueous ZIBs for large-scale energy applications. Image 1 Highlights: A spinel ZnV2 O4 is firstly introduced as a cathode material in aqueous zinc-ion battery. An electroactivation process is observed in initial charge-discharge cycles. The electroactivation results in an enhanced surface reaction and self-adaptive adjustment of lattice structure. PDF analysis offers insight into the structural evolution of the ZnV2 O4 at the atomic scale.